PROFESSIONAL EXAMINATIONS: ACCOUNTING PRACTICE. - Chamberlain, John H. (The Accounting Review, 1964)
The article presents a set of problems prepared by the Board of Examiners of the American Institute of Certified Public Accountants. It was presented at the second half of the CPA examination in accounting practice. The suggested time-frame has also been given. One of the problems provides the candidates with a printed worksheet. The candidates were asked to adjust the proprietorship's accounts for financial statement purposes, close the proprietorship's nominal accounts, and convert the proprietorship's accounts into the accounts with which the corporation will begin its operations. The candidates were provided a worksheet containing the trial balance with columns headed, Adjusting Entries, Pine Lumber Company Income Statement, Pine Lumber Company Balance Sheet, Closing and Conversion Entries, Pine Lumber Corporation Beginning Balances. The article presented another worksheet with condensed trial balances. The candidates were asked to prepare the formal journal entries at December 31, 1963 to record the change in accounting methods for 1963. They were to prepare a formal statement of income and retained earnings for the year ended December 31, 1963.